2020
DOI: 10.1186/s12957-020-01985-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant instant preoperative renal artery embolization facilitates the radical nephrectomy and thrombectomy in locally advanced renal cancer with venous thrombus: a retrospective study of 54 cases

Abstract: Background: The role of renal artery embolization (RAE) in the therapeutic armamentarium is always controversial. The present study aimed to assess the safety and the surgical outcomes of the instant renal artery embolization (I-RAE) prior to nephrectomy and thrombectomy in patients with locally advanced renal cell carcinoma (RCC) with venous thrombus. Methods: We performed a retrospective analysis of 54 patients treated with nephrectomy and thrombectomy between January 2012 and January 2019. Twenty-four patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Hydrogels are recognized for their distinctive importance and utility as drug delivery systems. Transarterial embolization of has been established as an efficacious method for expanding surgical options for RCC [ 106 ]. The significance of transarterial chemoembolization (TACE) in the palliative treatment of patients with malignant tumors is acknowledged [ 107 ].…”
Section: Materials Used For Rcc Treatmentmentioning
confidence: 99%
“…Hydrogels are recognized for their distinctive importance and utility as drug delivery systems. Transarterial embolization of has been established as an efficacious method for expanding surgical options for RCC [ 106 ]. The significance of transarterial chemoembolization (TACE) in the palliative treatment of patients with malignant tumors is acknowledged [ 107 ].…”
Section: Materials Used For Rcc Treatmentmentioning
confidence: 99%
“…During the nephrectomy, these patients had less estimated blood loss and transfusion requirements. However, there was no difference in the duration of operation, intensive care unit stay, hospital length of stay, or perioperative complications [ 57 ]. Another retrospective study found that patients with preoperative RAE had a 5-year survival rate of 62% and a 10-year survival rate of 47%, which was significantly higher than 35% and 23%, respectively, in the case-matched control group without RAE.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study from Cleveland Clinic demonstrated signi cant risk of perioperative mortality in patients with preoperative embolization (OR 5.5, p=0.03) as well as postoperative complications 13 . Recent study from Tang and colleagues, however, supported reduced blood loss and transfusion in patients receiving perioperative embolization(p<0.03) 14 . Notably, patients from Cleveland Clinic cohort had higher thrombus level when compared to Tang's study.…”
Section: Discussionmentioning
confidence: 97%